The impact of board characteristics and corporate ownership on corporate risk-taking: the case of Chinese listed companies - LI, JIEYU (2022)
Risk-taking can trace back as far as the entrepreneurial spirit of adventure. This paper refers to a company's willingness to invest, reflecting its choice of high-risk investment projects. As the central decision-making body linking shareholders and management, the board of directors has greater autonomy to make decisions while ensuring the rights and interests of shareholders. Therefore, there is a specific link between the board of directors and the risk-taking of the enterprise. In recent years, with the development of the economy, the participation of women in the labor market has gradually increased, and more women are entering the management organization of companies. And there may be significant differences in their risk appetite compared to men. For independent directors, independence and professionalism can provide good oversight and thus reduce the company's risk. Government intervention and policies can make a difference in the management and decision-making of the company due to the different nature of ownership.